Get-rich-quick scheme [innovative electricity conservation]. - Sweet, W.
This paper discusses how the New York-based company, ConsumerPowerline, is able to turn electricity conservation into a money-making venture. The idea behind ConsumerPowerline's business originated from a ruling in January 2000 by the US Federal Energy Regulatory Commission (FERC). By taking advantage of the New York Independent System Operator's Emergency Demand Response Program (EDRP), ConsumerPowerline can estimate precisely how much an organization stand to gain, based on its typical electricity usage, and how much electricity the organization can get along without for short periods. ConsumerPowerline gets reimbursed for its efforts when the organization starts to make money by not using electricity. Besides making the grid more reliable, local utilities do not have to build extra generators just to cover the highest peak loads for a few hours on the hottest days of the year.
Keywords: ConsumerPowerline; Emergency Demand Response Program; New York city; Electricity conservation; Energy shortage; Grid reliability; Investments; Peak loads; Utility economization